Reconceptualizing Conversion Disorder: A Rational-Choice Theory of Neurosis Perspective - Rofe, Yacov (Disease and Health Research: New Insights Vol. 11, 2024)
Conversion disorder remains enigmatic, with its understanding further complicated by the declining influence of psychoanalysis and emerging neurological insights suggesting biological underpinnings. Prevalent rates of this disorder vary widely across cultures and the population studied. Existing theories struggle to explain the efficacy of diverse interventions, such as psychoanalysis, behavior therapy, drug therapy, and religious therapy. This article reviews research and clinical evidence on the development and treatment of conversion disorder, proposing that this seemingly incompatible evidence can be integrated within a new framework: the Rational-Choice Theory of Neurosis (RCTN). RCTN builds on Freud's framework, introducing a new concept of repression and replacing the unconscious with self-deception while suggesting that neurotic disorders are rational behaviors. Repression is seen as a conscious coping mechanism which deliberately eliminates threatening stimuli from attention through the employment of distractive maneuvers. RCTN has already proven its integrative approach due to its ability to account for the differential efficacy of various therapeutic methods pertaining to neurosis, such as behavior therapy, religious therapy, cognitive-behavioral therapy (CBT), psychodynamic therapy and drugs, using one set of theoretical principals. This integration offers fresh insights into the condition and could enhance therapeutic approaches, making it a valuable contribution to the field.